Clinical characteristic, common sites, and geographical distribution of pediatric tuberculosis patients in Southwest China - Wang, Dong-Mei; Wang, Chuan; An, Qi; Yang, Qing; Liao, Yi (Frontiers in Pediatrics, 2024)
The data report of a large sample, dynamic epidemiology, and characteristic analysis of pediatric tuberculosis (TB) in southwest China is not clear. Herein, we conducted descriptive dynamic epidemiology, characteristic analysis and geographical distribution study of pediatric TB inpatients in southwest China for more than 20 years.: Patients with pediatric TB were recruited from October 2002 to September 2022 in southwest of China based on etiology or clinical confirmation. Extract hospitalization medical record information for each patient. The geographical distribution chart of cases is used to display the trend of case flow segmented every 5 years.Results: Among 3024 pediatric TB patients with an average age of 9.11 ± 4.39, 17.49% (529) had pulmonary tuberculosis (PTB), 9.06% (274) had extrapulmonary tuberculosis (EPTB), and 73.45% (2221) had combined TB. The most common form of EPTB is disseminated TB (28.98%), followed by TB lymphadenitis (20.56%), pleural TB (19.72%), and TB meningitis (19.68%). Children aged 0-4 years had a high risk of TB meningitis and a severe symptoms, while children in the elderly age group had a high risk of pleural TB. In the past 20 years, hospitalized TB pediatric cases mainly came from Sichuan, Tibet, Qinghai, Yunnan and other places. The number of patients from ethnic minorities, especially Tibetans, showed an upward trend on a yearly basis (χ 2 =401.43, P<0.001).Conclusions: Public health investment and effective management in pediatric TB should be further strengthened.